C / Co3O4 / TiO2 composite electrode material and preparation method thereof
By forming a p-n junction on the Co3O4 surface, TiO2 composite electrode material and deposition of TiO2 using atomic layer deposition technology, the problem of poor specific capacity and rate performance of Co3O4 is solved, and more efficient charge storage and transfer is achieved.
Patent Information
- Application Number
- CN202510795503.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-16
- Publication Date
- 2025-07-18
- Estimated Expiration
- 2045-06-16
AI Technical Summary
When Co3O4 is a supercapacitor electrode material, its specific capacity and rate performance are poor, which limits its practical application.
By forming a C/Co3O4/TiO2 composite electrode material with p-n junction on the Co3O4 surface, the n-type semiconductor TiO2 is deposited using atomic layer deposition technology to form a p-n junction to increase light absorption and a built-in electric field, and promote photogenerated charge separation and charge transfer.
The specific capacity and rate performance of the electrode are improved, and the problem of poor specific capacity and rate performance of Co3O4 is solved, achieving more efficient charge storage and transfer.
Smart Images

Figure CN120341054A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrochemical energy storage, and particularly relates to a C / Co3O4 / TiO2 composite electrode material with a p-n junction and a preparation method thereof. Background Art
[0002] Co3O4 is a typical pseudocapacitive material. Due to its easy preparation, low cost, stable performance, and high theoretical specific capacitance of 890 F / g, Co3O4 is an ideal supercapacitor electrode material. Its charge storage generates reversible redox in the Co 2+ / Co 3+ state, forming a layered CoOOH intermediate with a large interlayer spacing in Co(OH)2, which is beneficial to the embedding of ions during the charge storage process and has a battery-like Faraday behavior.
[0003] However, in the actual application process, the actual specific capacitance of Co3O4 is much lower than the theoretical value, and there is a large room for improvement. In addition, as a semiconductor, Co3O4 has poor conductivity and is not suitable for the rapid ion adsorption and desorption process, which greatly reduces the rate performance of the electrode material and limits its practical application. Summary of the Invention
[0004] The purpose of the present invention is to overcome the deficiencies of the prior art, and provide a Co3O4 composite electrode material with a p-n junction and a preparation method thereof, which solves the technical problems of poor specific capacitance and rate performance of the existing Co3O4.
[0005] To achieve the above purpose, the present invention adopts the following technical solutions: Referring to Figure 1 the synthesis route in the present invention provides a preparation method of a C / Co3O4 / TiO2 composite electrode material with a p-n junction, including the following steps:
[0006] In an acidic liquid, the carbon cloth is soaked, and oxygen-containing functional groups are grafted on the surface of the carbon cloth to obtain the activated carbon cloth; the cobalt source and the first oxygen source are used as deposition precursors, and the first deposition treatment is carried out by atomic layer deposition to deposit Co3O4 on the surface of the activated carbon cloth to obtain the C / Co3O4 composite electrode material; the titanium source and the second oxygen source are used as deposition precursors, and the second deposition treatment is carried out by atomic layer deposition to deposit TiO2 on the surface of the C / Co3O4 composite electrode material, and the p-type semiconductor Co3O4 and the n-type semiconductor TiO2 form a p-n junction to obtain the C / Co3O4 / TiO2 composite electrode material with a p-n junction.
[0006] The specific working principle of the present invention is as follows: The present invention uses atomic layer deposition technology to deposit n-type semiconductor TiO2 on the surface of Co3O4 to form a p-n junction. This p-n junction can not only increase the light absorption of TiO2, promote the separation of photo-generated charges, enable light energy to participate in the charge and discharge process of the electrode, and improve the specific capacity of the electrode; moreover, it can form an internal electric field, accelerate the redox reaction process, and promote the charge transfer reaction.
[0007] The possible action mechanism of the C / Co3O4 / TiO2 electrode is as follows: TiO2 + nhv → nh + + ne - 。
[0008] Photocatalytic-assisted charging process: TiO2 + Co3O4 + 4OH - + nhv → TiO2 + 3CoO2 + 2H2O + (n + 4) e - + nh + 。
[0009] Photocatalytic-assisted discharging process: TiO2 + 3CoO2 + 2H2O + nhv → TiO2 + Co3O4 + 4OH - + (n-4) e - + nh + 。
[0010] Optionally, the acidic liquid is sulfuric acid with a mass concentration of 30% to 70% or concentrated nitric acid with a mass concentration of 20% to 50%.
[0011] Optionally, the soaking time of the soaking treatment is 1d to 4d.
[0012] Optionally, the deposition temperature of the first deposition treatment is 150°C to 200°C, and the number of deposition cycles is 100 to 200 times.
[0013] Optionally, the deposition temperature of the second deposition treatment is 60°C to 200°C, and the number of deposition cycles is 5 to 20 times.
[0014] Optionally, the cobalt source is cobaltocene or cobalt acetylacetonate, and the first oxygen source is ozone or water.
[0015] Optionally, the titanium source is titanium isopropoxide or titanium tetrachloride, and the second oxygen source is water.
[0016] Optionally, the oxygen-containing functional group is at least one of hydroxyl, carboxyl, carbonyl, and ester groups. Specifically, the oxygen-containing functional group and the carbon cloth are mainly connected by covalent bonds or surface redox reactions.
[0017] Optionally, in the first deposition process, the pulse time of the cobalt source is 0.5 s, the exposure time is 10 s, and the purge time is 25 s; in the second deposition process, the pulse time of the titanium source is 0.5 s, the exposure time is 10 s, and the purge time is 25 s; in the first deposition process and the second deposition process, the pulse time of the first oxygen source and the second oxygen source is 1 s, the exposure time is 10 s, and the purge time is 25 s.
[0018] The present invention provides a C / Co3O4 / TiO2 composite electrode material with a p-n junction, which is prepared by using the preparation method of the C / Co3O4 / TiO2 composite electrode material with a p-n junction described above.
[0019] The beneficial effects of the present invention are as follows. Compared with the prior art, the present invention uses atomic layer deposition technology to first deposit Co3O4 on the surface of the activated carbon cloth, and then deposit the n-type semiconductor TiO2 on the surface of Co3O4 to form a p-n junction, thereby obtaining a C / Co3O4 / TiO2 composite electrode material with a p-n junction. This p-n junction can not only increase the light absorption of TiO2, promote the separation of photo-generated charges, enable light energy to participate in the charge-discharge process of the electrode, and improve the specific capacity of the electrode, but also form an internal electric field, accelerate the redox reaction process, and promote the charge transfer reaction. Therefore, the C / Co3O4 / TiO2 composite electrode material with a p-n junction has a high specific capacity and rate performance, thus solving the technical problems of poor specific capacity and rate performance of the existing Co3O4. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is a schematic diagram of the preparation process of a C / Co3O4 / TiO2 composite electrode material with a p-n junction provided by the present invention.
[0021] Figure 2 It is a scanning electron microscope image of the C / Co3O4 / TiO2 composite electrode material with a p-n junction prepared in Example 1 of the present invention at different magnification ratios. Among them, a is the scanning electron microscope image at a scale of 20 μm, b is the scanning electron microscope image at a scale of 10 μm, c is the scanning electron microscope image at a scale of 4 μm, and d is the scanning electron microscope image at a scale of 2 μm.
[0022] Figure 3 It is an X-ray diffraction pattern of the C / Co3O4 composite electrode material and the C / Co3O4 / TiO2 composite electrode material with a p-n junction prepared in Example 1 of the present invention.
[0023] Figure 4XPS characterization diagram of the C / Co3O4 / TiO2 composite electrode material with a p-n junction prepared in Example 1 provided by the present invention. Among them, a is the full XPS spectrum diagram, b is the high-resolution spectrum diagram of Co2p, c is the high-resolution spectrum diagram of O1s, and d is the high-resolution spectrum diagram of Ti 2p.
[0024] Figure 5 CV curve statistical chart of different composite electrode materials provided by the present invention in the scanning rate range of 5 mV / s to 100 mV / s. Among them, a is the CV curve statistical chart of the C / Co3O4 composite electrode material prepared in Example 1 in this scanning rate range, and b is the CV curve statistical chart of the C / Co3O4 / TiO2 composite electrode material with a p-n junction prepared in Example 1 in this scanning rate range.
[0025] Figure 6 CV curve statistical chart of different composite electrode materials provided by the present invention in the scanning rate range of 300 mV / s to 1000 mV / s. Among them, a is the CV curve statistical chart of the C / Co3O4 composite electrode material prepared in Example 1 in this scanning rate range, and b is the CV curve statistical chart of the C / Co3O4 / TiO2 composite electrode material with a p-n junction prepared in Example 1 in this scanning rate range.
[0026] Figure 7 CV curve statistical chart of different composite electrode materials provided by the present invention at scanning rates of 20 mV / s, 50 mV / s, 100 mV / s, and 300 mV / s. Among them, a is the CV curve statistical chart at a scanning rate of 20 mV / s, b is the CV curve statistical chart at a scanning rate of 50 mV / s, c is the CV curve statistical chart at a scanning rate of 100 mV / s, and d is the CV curve statistical chart at a scanning rate of 300 mV / s.
[0027] Figure 8 Relationship diagram between the specific capacitance and scanning speed of different composite electrode materials provided by the present invention.
[0028] Figure 9 Electrochemical performance characterization diagram of different composite electrode materials provided by the present invention. Among them, a is the CP curve diagram of the C / Co3O4 composite electrode material prepared in Example 1, b is the CP curve diagram of the C / Co3O4 / TiO2 composite electrode material with a p-n junction prepared in Example 1, c is the CP curve diagram of different composite electrode materials at a current density of 0.2 mA / cm 2 when, and d is the EIS curve diagram of different composite electrode materials under open circuit voltage. d1 is a partial enlarged schematic diagram in Figure d. Detailed implementation manners
[0029] To solve the above technical problems, the present invention provides a C / Co3O4 / TiO2 composite electrode material and a preparation method thereof. The technical solutions and embodiments of the present invention will be described in detail below with reference to the accompanying drawings.
[0030] The technical solutions adopted by the present invention are as follows: The present invention will be described in detail below through specific embodiments. The embodiments are exemplary and are intended to explain the present invention, but should not be construed as a limitation to the present invention.
[0031] Example 1 This example provides a preparation method of a C / Co3O4 / TiO2 composite electrode material with a p-n junction, including the following steps: In an acidic liquid, the carbon cloth is soaked. Oxygen-containing functional groups are grafted on the surface of the carbon cloth, and then the carbon cloth is taken out and washed three times with alcohol and deionized water to obtain the activated carbon cloth. Among them, the acidic liquid is concentrated nitric acid with a mass concentration of 50%, and the soaking time for the soaking treatment is 4 days.
[0032] Cobalt source and the first oxygen source are used as deposition precursors, and the first deposition treatment is carried out by atomic layer deposition to deposit Co3O4 on the surface of the activated carbon cloth to obtain a C / Co3O4 composite electrode material. Among them, the cobalt source is cobaltocene, the first oxygen source is ozone, the deposition temperature for the first deposition treatment is 200 °C, and the deposition cycle number is 200 times.
[0033] Titanium source and the second oxygen source are used as deposition precursors, and the second deposition treatment is carried out by atomic layer deposition to deposit TiO2 on the surface of the C / Co3O4 composite electrode material. The p-type semiconductor Co3O4 and the n-type semiconductor TiO2 form a p-n junction to obtain a C / Co3O4 / TiO2 composite electrode material with a p-n junction. Among them, the titanium source is titanium isopropoxide, the second oxygen source is water, the deposition temperature for the second deposition treatment is 60 °C, and the deposition cycle number is 10 times.
[0034] Example 2 This example provides a preparation method of a C / Co3O4 / TiO2 composite electrode material with a p-n junction. The difference from Example 1 is that the cobalt source is acetylacetone and the first oxygen source is water.
[0035] Example 3 This example provides a preparation method of a C / Co3O4 / TiO2 composite electrode material with a p-n junction. The difference from Example 1 is that the titanium source is titanium tetrachloride.
[0036] Example 4 This embodiment provides a method for preparing a C / Co3O4 / TiO2 composite electrode material with a p-n junction. The difference from Example 1 is that the cobalt source is acetylacetone and the first oxygen source is water.
[0037] Example 5 This embodiment provides a method for preparing a C / Co3O4 / TiO2 composite electrode material with a p-n junction. The difference from Example 1 is that the deposition temperature of the first deposition treatment is 150 °C.
[0038] Example 6 This embodiment provides a method for preparing a C / Co3O4 / TiO2 composite electrode material with a p-n junction. The difference from Example 1 is that the number of deposition cycles of the first deposition treatment is 100 times.
[0039] Example 7 This embodiment provides a method for preparing a C / Co3O4 / TiO2 composite electrode material with a p-n junction. The difference from Example 1 is that the deposition temperature of the second deposition treatment is 200 °C.
[0040] Example 8 This embodiment provides a method for preparing a C / Co3O4 / TiO2 composite electrode material with a p-n junction. The difference from Example 1 is that the number of deposition cycles of the second deposition treatment is 5 times.
[0041] Example 9 This embodiment provides a method for preparing a C / Co3O4 / TiO2 composite electrode material with a p-n junction. The difference from Example 1 is that the number of deposition cycles of the second deposition treatment is 20 times.
[0042] Example 10 This embodiment provides a method for preparing a C / Co3O4 / TiO2 composite electrode material with a p-n junction. The difference from Example 1 is that the acidic liquid is concentrated nitric acid with a mass concentration of 20%.
[0043] Example 11 This embodiment provides a method for preparing a C / Co3O4 / TiO2 composite electrode material with a p-n junction. The difference from Example 1 is that the acidic liquid is sulfuric acid with a mass concentration of 30%.
[0044] Example 12 This embodiment provides a method for preparing a C / Co3O4 / TiO2 composite electrode material with a p-n junction. The difference from Example 1 is that the acidic liquid is sulfuric acid with a mass concentration of 70%.
[0045] Example 13 This embodiment provides a method for preparing a C / Co3O4 / TiO2 composite electrode material with a p-n junction. The difference from Example 1 is that the soaking time for the soaking treatment is 1 day.
[0046] It should be noted that compared with Example 1, there is no obvious difference in the performance of the C / Co3O4 / TiO2 composite electrode materials with p-n junctions prepared in Examples 2 to 13.
[0047] Using this electrode as the working electrode, saturated calomel as the reference electrode, and a platinum sheet as the counter electrode, a three-electrode system was assembled for cyclic voltammetry testing, galvanostatic charge-discharge testing, and AC impedance testing.
[0048] Material surface morphology characterization tests and results The C / Co3O4 composite electrode material and the C / Co3O4 / TiO2 composite electrode material with a p-n junction prepared in Example 1 were respectively subjected to scanning electron microscopy testing, X-ray diffraction testing, and XPS spectroscopy testing to characterize the surface morphology of the materials.
[0049] The test results are as follows: Figure 2 These are scanning electron microscope images of the C / Co3O4 / TiO2 composite electrode material with a p-n junction at different magnifications provided by the present invention. It can be seen from Figures a to d that a large number of granular materials are evenly distributed in the gaps of the carbon cloth fibers. The particle size of the granular materials is approximately between 2 µm and 5 µm. The granular materials are p-n junction composite materials formed by Co3O4 and TiO2 through deposition treatment.
[0050] Figure 3 These are the X-ray diffraction patterns of the C / Co3O4 composite electrode material and the C / Co3O4 / TiO2 composite electrode material with a p-n junction provided by the present invention. It can be seen from the figure that the diffraction peaks of the two samples at 2θ are both around 24.8°. This is mainly the characteristic peak of the carbon cloth, indicating that the C / Co3O4 composite electrode material and the C / Co3O4 / TiO2 composite electrode material with a p-n junction mainly exist in an amorphous form.
[0051] The chemical composition and state of the C / Co3O4 / TiO2 composite electrode material with a p-n junction prepared in Example 1 were studied using XPS spectroscopy. The results are as Figure 4 shown.
[0052] Among them, the XPS full spectrum of the C / Co3O4 / TiO2 composite electrode material is shown in Figure a. It can be seen from the figure that there is a main peak at the binding energies of 287.94 eV, 531.88 eV, 781.85 eV, and 454.1 eV in the sample, corresponding to the XPS spectra of C1s, O1s, Co2p, and Ti2p respectively, indicating the successful preparation of Co3O4 / TiO2 and no other impurities in the prepared sample.
[0053] Specifically, the XPS spectrum of Co2p is shown in Figure b. It can be seen from the figure that there are two main peaks at 780.3 eV and 795.1 eV, corresponding to Co2p3 / 2 and Co2p1 / 2 respectively, and there are two satellites at 789.8 eV and 803.5 eV, which are the characteristics of the Co3O4 phase. The Co2p3 / 2 peak with a binding energy of 780.3 eV can be decomposed into two fitting peaks at 780.3 eV and 784.7 eV, while the Co2p3 / 2 peak with a binding energy of 795.1 eV can be decomposed into two fitting peaks at 794.8 eV and 798.8 eV.
[0054] The high-resolution O1s spectrum in Figure c shows three fitting peaks corresponding to Co-O-Co / Ti-O-Ti at 531.1 eV, Co-O-H / Ti-O-H at 531.7 eV, and C-O / C=O at 532.9 eV, confirming the presence of lattice oxygen, hydroxyl oxygen, and surface oxygen on the surface. Among them, the characteristic peaks at 531.1 eV and 531.7 eV belong to the lattice oxygen and hydroxyl oxygen in TiO2 and Co3O4, and the characteristic peak at 532.9 eV corresponds to the oxygen adsorbed on the surface of the composite electrode material. The adsorbed oxygen mainly comes from the absorption of hydroxyl, water, or oxygen by the oxygen vacancies on the sample surface, indicating that grafting oxygen-containing functional groups on the surface of carbon cloth can indeed be achieved by soaking the carbon cloth. These oxygen vacancies can inhibit the recombination of carriers, thereby improving the optoelectronic activity of the semiconductor.
[0055] The XPS spectrum of Ti2p is shown in Figure d. It can be seen from the figure that the peaks at 458.7 eV and 464.4 eV correspond to the binding energies of Ti2p3 / 2 and Ti2p1 / 2 respectively, indicating that the main state of Ti element in this sample is Ti 4+ 。
[0056] Electrochemical performance characterization tests and results The C / Co3O4 composite electrode material prepared in Example 1 and the C / Co3O4 / TiO2 composite electrode material with a p-n junction were used as the working electrode, saturated calomel as the reference electrode, and platinum sheet as the counter electrode to assemble a three-electrode system for cyclic voltammetry testing, galvanostatic charge-discharge testing, and AC impedance testing.
[0057] The test results are as follows: Figure 5 CV curve statistical charts of different composite electrode materials provided by the present invention in the scanning rate range of 5 mV / s to 100 mV / s Figure 6 CV curve statistical charts of different composite electrode materials provided by the present invention in the scanning rate range of 300 mV / s to 1000 mV / s. It can be seen from the figure that as the scanning rate increases, the distortion shapes of the CV diagrams of the C / Co3O4 composite electrode material and the C / Co3O4 / TiO2 composite electrode material basically remain unchanged, and still present a good rectangular shape at a large scanning rate. That is, when the voltage changes direction, the current will quickly reach the maximum value, indicating that the charge and discharge speeds of both materials are relatively fast and they have excellent capacitance performance.
[0058] Figure 7 CV curve statistical charts of different composite electrode materials provided by the present invention at scanning rates of 20 mV / s, 50 mV / s, 100 mV / s, and 300 mV / s. It can be seen from the figure that when the scanning rate is 20 mV / s, there is a pair of redox peaks on the CV curve diagrams of the C / Co3O4 composite electrode material and the C / Co3O4 / TiO2 composite electrode material. The possible surface oxidation reaction is: Co3O4 + OH - + H2O → 3CoOOH + e - ; CoOOH + OH - → CoO2 + H2O + e - .
[0059] The possible reduction reaction is: CoO2 + H2O + e - → CoOOH + OH - ; 3CoOOH + e - → Co3O4 + OH - + H2O.
[0060] After the scanning rate increases to 50, 100, 300 mV / s, the redox peaks on the CV curve of the C / Co3O4 composite electrode material are significantly weakened or even disappear, but the redox peaks still exist on the CV curve of the C / Co3O4 / TiO2 composite electrode material. This is because when the scanning rate increases, the reaction rate speeds up and ions do not have time to undergo redox reactions. Therefore, after the scanning rate increases, the oxidation and reduction reaction peaks on the CV curve of the C / Co3O4 composite electrode material gradually disappear. However, when TiO2 is added, since Co3O4 is a p-type semiconductor and TiO2 is an n-type semiconductor, a p-n junction will be formed between them. The p-n junction will form a built-in electric field to promote charge transfer and accelerate the charge and discharge speed. Therefore, the redox peaks of the CV curve of the C / Co3O4 / TiO2 composite electrode material with a p-n junction do not disappear.
[0061] It can be seen from Figure 8 that as the scanning rate increases, the specific capacitances of both the C / Co3O4 composite electrode material and the C / Co3O4 / TiO2 composite electrode material show a downward trend. Under the same scanning rate condition, the specific capacitance of the C / Co3O4 / TiO2 composite electrode material is larger than that of the C / Co3O4 composite electrode material. For example, when the scanning rate is 5 mV / s, the specific capacitance of the C / Co3O4 / TiO2 composite electrode material increases from 13.4 mF / cm 2 to 16.3 mF / cm 2 . This is because under the action of light, a pair of electrons and holes are generated in the semiconductor TiO2. The generated holes oxidize Co3O4 in Co3O4 / TiO2 to CoO2, promoting the separation of photo-generated charges. The light energy participates in the charge and discharge process of the electrode, improving the specific capacitance of the electrode.
[0062] Figure 9 The electrochemical performance characterization diagrams of different composite electrode materials provided by the present invention. It can be seen from Figures a and b that the CP curves of the C / Co3O4 composite electrode material and the C / Co3O4 / TiO2 composite electrode material at different scanning speeds all show an isosceles triangle-like shape, indicating that the charge and discharge processes of both materials are reversible and both have excellent electrochemical energy storage characteristics. At the same current density, the discharge time of the C / Co3O4 / TiO2 composite electrode material is longer than that of the C / Co3O4 composite electrode material. According to the electrode calculation formula, the longer the discharge time, the larger the specific capacitance of the electrode, that is, it shows that the C / Co3O4 / TiO2 composite electrode material has a larger specific capacitance.
[0063] Among them, Figure c is for different composite electrode materials at a current density of 0.2 mA / cm 2CP curve at that time. It can be seen from the figure that, compared with the C / Co3O4 composite electrode material, the charging and discharging process times of the C / Co3O4 / TiO2 composite electrode material formed after TiO2 modification both increase, indicating that TiO2 has an impact on the entire electrode charging and discharging process. TiO2 has good catalytic activity. It can absorb visible light and generate holes and electrons under the action of an electric field. The holes and electrons respectively participate in the charging and discharging process of the electrode, increasing its capacity. The possible action mechanism of the C / Co3O4 / TiO2 electrode is as follows:
[0064] TiO2 + nhv → nh + + ne - 。
[0065] Photocatalytic-assisted charging process: TiO2 + Co3O4 + 4OH - + nhv → TiO2 + 3CoO2 + 2H2O + (n + 4) e - + nh + 。
[0066] Photocatalytic-assisted discharging process: TiO2 + 3CoO2 + 2H2O + nhv → TiO2 + Co3O4 + 4OH - + (n - 4) e - + nh + 。
[0067] Among them, h + represents photogenerated holes, e - represents photogenerated electrons or free electrons in the oxidation / reduction reaction, and n is the number of photogenerated carriers. As the light irradiation increases the number of photogenerated carriers from 0 to n, more electrons are stored as charges and separated from the holes through the built-in electric field formed by the p-n junction. Therefore, the specific capacity increases.
[0068] The AC impedance curves of the C / Co3O4 composite electrode material and the C / Co3O4 / TiO2 composite electrode material at open circuit voltage are shown in Figure d. It can be seen from the figure that the charge transfer resistance Rct and the equivalent resistance Rs of the C / Co3O4 / TiO2 composite electrode material are both smaller than those of the C / Co3O4 composite electrode material. This may be due to the built-in electric field formed by the p-n junction, which accelerates the oxidation-reduction reaction process and reduces the equivalent internal resistance of the electrode material.
[0069] The above-described are only the preferred embodiments of the present invention, and the above specific embodiments are not limitations to the present invention. Within the scope of the technical idea of the present invention, various deformations and modifications may occur. Any retouching, modification or equivalent replacement made by those of ordinary skill in the art according to the above description shall fall within the scope protected by the present invention.
Claims
1. A preparation method of a C / Co3O4 / TiO2 composite electrode material with a p-n junction, characterized in that, It includes the following steps: In an acidic liquid, the carbon cloth is subjected to an immersion treatment, and oxygen-containing functional groups are grafted onto the surface of the carbon cloth to obtain an activated carbon cloth; Cobalt source and the first oxygen source are used as deposition precursors, and the first deposition treatment is carried out by atomic layer deposition to deposit Co3O4 on the surface of the activated carbon cloth to obtain a C / Co3O4 composite electrode material; Titanium source and the second oxygen source are used as deposition precursors, and the second deposition treatment is carried out by atomic layer deposition to deposit TiO2 on the surface of the C / Co3O4 composite electrode material. The p-type semiconductor Co3O4 and the n-type semiconductor TiO2 form a p-n junction to obtain a C / Co3O4 / TiO2 composite electrode material with a p-n junction.
2. The preparation method of the C / Co3O4 / TiO2 composite electrode material with a p-n junction according to claim 1, characterized in that, The acidic liquid is sulfuric acid with a mass concentration of 30% - 70% or concentrated nitric acid with a mass concentration of 20% - 50%.
3. The preparation method of the C / Co3O4 / TiO2 composite electrode material with a p-n junction according to claim 2, characterized in that, The immersion time of the immersion treatment is 1d - 4d.
4. The preparation method of the C / Co3O4 / TiO2 composite electrode material with a p-n junction according to claim 1, characterized in that, The deposition temperature of the first deposition treatment is 150°C - 200°C, and the number of deposition cycles is 100 times - 200 times.
5. The preparation method of the C / Co3O4 / TiO2 composite electrode material with a p-n junction according to claim 1, characterized in that, The deposition temperature of the second deposition treatment is 60°C - 200°C, and the number of deposition cycles is 5 times - 20 times.
6. The preparation method of the C / Co3O4 / TiO2 composite electrode material with a p-n junction according to claim 1, characterized in that, The cobalt source is cobaltocene or cobalt acetylacetonate, and the first oxygen source is ozone or water.
7. The preparation method of the C / Co3O4 / TiO2 composite electrode material with a p-n junction according to claim 1, characterized in that, The titanium source is titanium isopropoxide or titanium tetrachloride, and the second oxygen source is water.
8. The preparation method of the C / Co3O4 / TiO2 composite electrode material with a p-n junction according to claim 1, characterized in that, The oxygen-containing functional group is at least one of hydroxyl group, carboxyl group, carbonyl group and ester group.
9. The preparation method of the C / Co3O4 / TiO2 composite electrode material with a p-n junction according to claim 1, characterized in that, In the first deposition treatment, the pulse time of the cobalt source is 0.5s, the exposure time is 1s, and the purge time is 25s; In the second deposition treatment, the pulse time of the titanium source is 1s, the exposure time is 1s, and the purge time is 25s; In the first deposition treatment and the second deposition treatment, the pulse time of the first oxygen source and the second oxygen source is 1s, the exposure time is 1s, and the purge time is 25s.
10. A C / Co3O4 / TiO2 composite electrode material with a p-n junction, characterized in that, It is prepared by using the preparation method of the C / Co3O4 / TiO2 composite electrode material with a p-n junction according to any one of claims 1 - 9.
Citation Information
Patent Citations
Cobaltosic oxide porous microsphere, preparation method thereof and application of cobaltosic oxide porous microsphere in photo-assisted supercapacitor
CN113044887A
METHOD OF FORMING Co3O4 THIN FILM
KR1020180066311A